2003
DOI: 10.1179/016164103101201229
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Cullin-5 mRNA levels in the rat central nervous system following hemorrhagic shock

Abstract: Hemorrhagic shock is a clinical syndrome that manifests as hypoperfusion, hypoxia, and ischemia initiating various cellular stress responses involved in the synthesis and release of an assortment of pro-inflammatory molecules, cytokines, chemokines, and reactive oxidant species (ROS). The ROS have been shown to oxidize and damage proteins making them targets for ubiquitination and proteasomal degradation. Cullin-5 (cul-5), an E3 ligase that binds ubiquitin to proteins targeted for degradation via the proteasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A 1.6-fold change in Cul5 mRNA expression, and a 6.5-fold change in Cul5 protein expression, may have an important role in cellular processes such as differentiation since a previous study indicated that a less than twofold increase in the expression of another cullin family member, Cul4A, promotes proliferation and attenuates granulocytic differentiation of the PLB-985 human myeloid leukemia cell line . Other studies have shown similar fold changes in Cul5 expression in some rat tissues following hemorrhagic shock, traumatic brain injury, and osmotic stress (Ceremuga et al 2003a, b;Yao et al 2006). It is also of interest that a recent study showed a decrease in Cul5 mRNA expression in B-cell chronic lymphocytic leukemia (Kalla et al 2007).…”
Section: Discussionmentioning
confidence: 94%
“…A 1.6-fold change in Cul5 mRNA expression, and a 6.5-fold change in Cul5 protein expression, may have an important role in cellular processes such as differentiation since a previous study indicated that a less than twofold increase in the expression of another cullin family member, Cul4A, promotes proliferation and attenuates granulocytic differentiation of the PLB-985 human myeloid leukemia cell line . Other studies have shown similar fold changes in Cul5 expression in some rat tissues following hemorrhagic shock, traumatic brain injury, and osmotic stress (Ceremuga et al 2003a, b;Yao et al 2006). It is also of interest that a recent study showed a decrease in Cul5 mRNA expression in B-cell chronic lymphocytic leukemia (Kalla et al 2007).…”
Section: Discussionmentioning
confidence: 94%
“…ER-α is ubiquitinated and degraded in the proteasome [28, 29]. Cerebral ischemia is known to alter proteasomal activity [30, 31], suggesting the possibility that changes in the rate of receptor degradation might alter the concentration of receptor protein relative to receptor mRNA in the hours following BCO. At the mRNA level, ER-α mRNA is rapidly degraded [32]; the rate of degradation is influenced by binding of RNA-binding proteins to 3′ terminal AU-rich regions [33].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially evocative, as extracellular ubiquitin and elements of the ubiquitin signaling pathway 28 are not only known to be enhanced in patients after multiple injuries in general, 29 but—if applied for therapeutic reasons—seem to reduce fluid requirements in a experimental hemorrhage mouse model. 30 Furthermore, extracellular ubiquitin seems to have antiinflammatory properties and may be involved in immunosuppressive mechanisms in critical ill patients.…”
Section: Discussionmentioning
confidence: 99%